TcSERPIN, an inhibitor that interacts with cocoa defense proteins and has biotechnological potential against human pathogens - Ferreira, Monaliza Macêdo; Farias, Keilane Silva; Zugaib, Maria; Alves, Akyla Maria Martins; Amaral, Geiseane Velozo; Santos, Maria Luíza do Carmo; Freitas, Andria dos Santos; Santana, Brenda Conceição Guimarães; dos Santos Júnior, Sérgio Liberato; Mora-Ocampo, Irma Yuliana; Santos, Ariana Silva; da Silva, Marcelo Fernandes; et al. (Frontiers in Plant Science, 2024)
In plants, serpins are a superfamily of serine and cysteine protease inhibitors involved in stress and defense mechanisms, with potential for controlling agricultural pests, making them important biotechnological tools. The objective of this study was to characterize a serpin from Theobroma cacao, called TcSERPIN, to identify its endogenous targets and determine its function and biotechnological potential. TcSERPIN has 390 amino acid residues and shows conservation of the main active site, RCL. Cis-elements related to light, stress, hormones, anaerobic induction, cell cycle regulation and defense have been identified in the gene's regulatory region. TcSERPIN transcripts are accumulated in different tissues of Theobroma cacao. Furthermore, in plants infected with Moniliophtora perniciosa and Phytophthora palmivora, the expression of TcSERPIN was positively regulated. The protein spectrum, rTcSERPIN, reveals a typical β-sheet pattern and is thermostable at pH 8, but loses its structure with temperature increases above 66 °C at pH 7. At the molar ratios of 0.65 and 0.49, rTcSERPIN inhibited 55 and 28% of the activity of papain from Carica papaya and trypsin from Sus scrofa, respectively. The protease trap containing immobilized rTcSERPIN captured endogenous defense proteins from cocoa extracts that are related to metabolic pathways, stress and defense. The evaluation of the biotechnological potential against geohelminth larvae showed that rTcSERPIN and rTcCYS4 (Theobroma cacao cystatin 4) reduced the movement of larvae after 24 hours.The results of this work show that TcSERPIN has ideal biochemical characteristics for biotechnological applications, as well as potential for studies of resistance to phytopathogens of agricultural crops.